Meningkatkan Kinerja Karyawan Dengan Budaya Organisasi Melalui Motivasi Berprestasi Dan Pemberdayaan Karyawan (Studi di Hotel Le Dian – Kota Serang) - Hadi, Samsul; Ramdansyah, Agus David (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
The research objective is to find out how Le Dian Hotel can carry out its commitment to provide quality service to every guest represented in an organizational culture so that it can make employees more motivated to achieve maximum work performance and performance assisted by optimal empowerment. The research object was the employees of Hotel Le Dian, Serang with a total sample of 100 people. Data analysis using SEM-PLS model. The results showed that there was a positive influence of organizational culture on employee performance and achievement motivation. There is a positive influence of achievement motivation on employee performance and there is a positive moderation of empowerment on the relationship between achievement motivation and employee performance. This research implies the importance of organizational culture at Le Dian Hotel to be able to improve employee performance which is strengthened by high achievement motivation and employee empowerment